Dramaturgies of participation. La Trilogia della guerra: Collaborating in the Staging of the Tragic - Federico Boni (piano b)
This article aims to explore how theatre can fully express its potential within a participatory and political framework, presenting the initial findings of an ethnographic study focused on the main ways in which a theatrical performance can create an aesthetic and political forum. The performances under investigation were developed by a young theatre company whose work is rooted in collaborative methods and audience participation. The ethnographic research presented here is based on participant observation of both the creative practices of the performers and the engagement of audiences in three recent productions directed by Gabriele Vacis with the theatre company PoEM (Potenziali Evocati Multimediali): Prometeo (2022), Antigone e i suoi fratelli (2023), and Sette a Tebe (2023). These three productions were staged as part of the Teatro Stabile di Torino’s season from November 30, 2023, to December 17, 2024, and collectively framed as a “Trilogy of War.” The research identifies three key aspects as particularly significant: the participatory relationship between actors and audiences during performances; the collaboration between professional theatre-makers and individuals traditionally excluded from the creative process of the performing arts; and finally, the pedagogical project through which performance becomes a space for reflecting on democracy, its contradictions, and its ambiguities.